Epididymal Primary Mast Cell Tumor in a Dog - Magalhães, Geórgia Modé; Léga, Elzylene; Torres-Neto, Rafael; Conforti, Valéria Amorim; Amorim, Renée Laufer [UNESP]; Marques, Camila Ângela; Rocha, Thaís Gomes; Honsho, Cristiane dos Santos (Universidade Federal do Rio Grande do Sul, 2023)
Background: In the literature, there are a few descriptions of epididymis neoplasia in domestic animals, especially considering primary tumors. In the few reports found in literature, the lesions were a consequence of the invasion of testicular or paratesticular neoplasia, as a papillar carcinoma in a dog’s and a bull’s epididymis, and mesenchymal tumors - fibrome/ fibrosarcoma, leiomyoma/leiosarcome. On the other hand, mast cell tumors are the second most prevalent neoplasia in dogs in Brazil, affecting especially the skin. The aim of this report is to describe for the first time a low malignancy mast cell tumor in a mixed-breed dog’s epididymis, without metastasis or recurrence in a 2-year follow-up period. Case: A 10-year-old male mixed-breed dog was presented for pre-surgical evaluation for elective orchiectomy. In the physical examination, an increase in the volume of approximately 2 cm with an irregular appearance was identified on palpation in the cranial pole of the left testis. In the trans surgical period, an increase in testicular volume (4 cm long x 2 cm wide) was observed, with a firm consistency in the region of the vas deferens with macroscopic changes in the region. The testis was sectioned, and the fragments were sent for histopathological evaluation in 10% buffered formaldehyde. There was a fairly cellular circumscribed neoplastic infiltrate, distributed in a sheet and separated by fibrovascular stroma, and rounded neoplastic cells with a moderate amount of basophilic cytoplasmic granulation, and discrete anisocytosis and anisokaryosis. The nuclei were rounded with vesicular chromatin with 1 or 2 distinct nucleoli. No mitosis figures were observed in 10 high power fields (400x). Few eosinophils were distributed throughout the neoplastic cell population. Immunohistochemistry demonstrated immunostaining for KIT protein with perimembranous staining in 95% of neoplastic mast cells, giving a KIT 1 pattern. There was no positive nuclear staining for Ki67 in any cell of the histological sections examined. A grade II mast cell tumor (low grade of malignancy) was diagnosed. After diagnosis, the animal underwent radiographic evaluation of the chest and abdominal ultrasound, and a new physical inspection in search of nodules, plaques, skin lesions, or subcutaneous masses. There were no metastases in the thorax and abdominal cavity, nor physical alterations, and it can be inferred that the epididymis was the primary site of the mast cell tumor. After 2 years of orchiectomy, there were no recurrences, and no chemotherapy treatment was performed. Discussion: Extracutaneous mast cell tumors are uncommon in animals, but have been reported in oral and nasal mucosa, nasopharynx, larynx, trachea, intestine, visceral lymph nodes, spleen, liver, spinal cord, intestine, ureter, conjunctiva, lung and more recently in tear gland of the third eyelid. However, in the authors’ assessment, this is the first description of mast cell tumor in the epididymis in dogs. The diagnosis was established by histopathological examination, which revealed a grade II epididymal mast cell tumor and immunohistochemical evaluation (KIT and Ki-67) as being of low aggressiveness. The diagnosis of a primary tumor was confirmed since the staging was established after the histopathological diagnosis, involving chest radiography, abdominal ultrasound, cutaneous evaluation in search of nodules, plaques, cutaneous and subcutaneous lesions, and did not reveal other abnormalities or metastases not identified in the preoperative evaluation. In addition, immunostaining with KIT and Ki-67 reaffirmed the low degree of malignancy and the potential for metastases, which can be observed by the asymptomatic follow-up of the patient 2 years after the surgical excision.
Keywords: carcinoma; histopathology; immunohistochemistry; metastases; neoplasm; tumoral